2020
DOI: 10.5194/acp-20-10073-2020
|View full text |Cite
|
Sign up to set email alerts
|

Radiative heating rate profiles over the southeast Atlantic Ocean during the 2016 and 2017 biomass burning seasons

Abstract: Abstract. Marine boundary layer clouds, including the transition from stratocumulus to cumulus, are poorly represented in numerical weather prediction and general circulation models. Further uncertainties in the cloud structure arise in the presence of biomass burning carbonaceous aerosol, as is the case over the southeast Atlantic Ocean, where biomass burning aerosol is transported from the African continent. As the aerosol plume progresses across the southeast Atlantic Ocean, radiative heating within the aer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…A negative buoyancy, generated at the top of these layers, can aid downward mixing. Although the longwave cooling from the additional water vapor transported within the aerosol layers is typically small compared to that from the aerosol shortwave absorption (Marquardt Collow et al, 2020), the vertical structure of the radiative heating is also altered, with most of the longwave cooling occurring above the maximum in the shortwave heating from aerosol. It is this displacement that helps maintain a better mixed aerosol or humidity layer.…”
Section: October: Increased Cloud Cover On Smokier Daysmentioning
confidence: 99%
“…A negative buoyancy, generated at the top of these layers, can aid downward mixing. Although the longwave cooling from the additional water vapor transported within the aerosol layers is typically small compared to that from the aerosol shortwave absorption (Marquardt Collow et al, 2020), the vertical structure of the radiative heating is also altered, with most of the longwave cooling occurring above the maximum in the shortwave heating from aerosol. It is this displacement that helps maintain a better mixed aerosol or humidity layer.…”
Section: October: Increased Cloud Cover On Smokier Daysmentioning
confidence: 99%
“…MERRA-2 datasets are given on a nominal 50 km horizontal resolution (0.5 • × 0.5 • ) with 72 vertical layers from the surface to 0.01 hPa. An additional goal of the ORACLES campaign was to evaluate chemical transport models and reanalysis products such as MERRA-2, and to this end the complete set of MERRA-2 files has been sampled up to a 1 s resolution along every ORACLES flight (Collow et al, 2020). These products are available online at https://portal.nccs.nasa.gov/datashare/ iesa/campaigns/ORACLES/.…”
Section: Merra-2mentioning
confidence: 99%
“…The authors of that study also showed that differences in longwave cooling were more strongly associated with the free tropospheric water vapor signal than with the cloud thickness itself, which illustrates the strong radiative potential of water vapor in this region. Recently, Marquardt Collow et al (2020) used data from the LASIC (Layered Atlantic Smoke Interactions with Clouds) field campaign based at Ascension Island (7.96 • S, 14.35 • W) in conjunction with Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2), reanalysis and a radiative transfer model to quantify the radiative heating rate due to aerosols and clouds for July through October of 2016 and 2017. They found strong cloud-top longwave cooling and strong cloud-top shortwave heating due to absorbing aerosols, with a monthly mean maximum heating rate of 2.1-2.4 K/d in September 2016 (approximately double the heating rate found by Adebiyi et al, 2015, over St Helena).…”
Section: Introductionmentioning
confidence: 99%
“…Several multi-national and multi-agency efforts have investigated the Southern Hemisphere with respect to aerosols, clouds, precipitation, and meteorological patterns during the 2016-2017 period. A recent field campaign, Layered Atlantic Smoke Interactions with Clouds (LASIC), featured the deployment of a U. S. Department of Energy Atmospheric Radiation Measurement (ARM) mobile facility (AMF) along with surface, satellite, and aircraft measurements (Kacarab et al, 2020;Marquardt Collow et al, 2020;Ryoo et al, 2021Ryoo et al, , 2022Zuidema et al, 2016).…”
Section: Research Article 101029/2023ea003138mentioning
confidence: 99%